DETERMINAN FINANCIAL DISCLOSURE: TINJAUAN LITERATUR TERHADAP TRANSPARANSI DAN KINERJA PERUSAHAAN - Fifi Rahma Dwiyanti; Dwi Cahyono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
This study aims to develop a conceptual model of the determinants of financial disclosure and their implications for corporate transparency and firm performance. A qualitative approach was employed using a systematic literature review of 47 articles published in reputable international journals between 2001 and 2025. The articles were selected through keyword-based searches, inclusion and exclusion criteria, and thematic synthesis to identify key themes, relationships, and research gaps. The review identifies five major determinants of financial disclosure: corporate governance, firm characteristics (size, leverage, profitability, and firm age), environmental, social, and governance (ESG) performance, the regulatory environment, and digital technology adoption, including XBRL, internet-based reporting, and artificial intelligence. The findings indicate that financial disclosure is influenced by both internal organizational factors and external institutional and technological developments. High-quality financial disclosure improves corporate transparency by reducing information asymmetry between management and stakeholders, thereby supporting better firm performance. This study contributes to the literature by integrating fragmented findings into a comprehensive conceptual framework that explains the relationships among the determinants of financial disclosure and their outcomes. The proposed framework provides a useful foundation for future empirical research and offers practical insights for managers, regulators, auditors, and other stakeholders seeking to strengthen corporate transparency and accountability.